THE EFFECT OF VARIOUS TYPES OF ORGANIC FERTILIZER ON THE GROWTH AND PRODUCTION OF GREEN BEAN (Vigna radiata L.) - Asmara Sari Nasution (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The research of the effect of various types of organic fertilizer on the growth and yield of mung bean (Vigna radiata l.) has been carried out by using a randomized block design with 2 factors and 3 replications. The analytical methods used to conclute derived from the analysis of data by using a linear mathematical model. The observed parameters were plant height, stem diameter, number of productive branches, number of pods / plant and 100-seed weight. Provision of various types of organic fertilizers, organic fertilizers dose, as well as interaction not significant effect on all parameters observed.Keywords: organic fertilizer, growth, yield, mung bean